Politik Hukum Pembentukan Badan Pembina Ideologi Pancasila - Rifqy, Muhammad; Indra, Mexsasai; Zulwisman, Zulwisman (Jurnal Ilmiah Wahana Pendidikan, 2025)
The position of Pancasila in the Indonesian legal system is as the source of all sources of state law. The Pancasila Ideology Development Agency (BPIP) is an agency that was built as a form of re-actualization of Pancasila in the process of internalizing values ​​in every component of society and state administrators. The main tasks and functions of BPIP are actually included in the main tasks and functions of other state institutions. This overlapping of duties and functions causes pros and cons in society. Pros and cons of establishing BPIP, whose duties and functions should have been carried out by the MPR. As a result of the overlapping of BPIP's main tasks and functions with other state institutions, it certainly puts a burden on the state budget, which can lead to wastage of the state budget. The type of legal research is normative legal research. The data used is secondary data. Meanwhile, if you look at the nature of this research, it is descriptive. The results of this research are the legal politics of establishing the Pancasila Ideology Development Agency based on the legal basis of Presidential Regulation Number 7 of 2018 concerning the Pancasila Ideology Development Agency. The urgency of establishing BPIP still needs to be questioned and the effectiveness of BPIP is still doubtful. The correlation between the duties of the Pancasila Ideology Development Agency which overlaps with the duties of the Indonesian MPR is that the duties and functions of the BPIP have become the duties of a high state institution, namely the People's Consultative Assembly (MPR), which also has the same duties, namely promoting Pancasila, the 1945 Constitution and its implementation. There is an overlap in duties and functions, effectiveness and efficiency, between the BPIP and the MPR which means that the position of the BPIP in the Indonesian constitutional system is still unclear. The ideal concept of fostering the Pancasila ideology in Indonesia is through the high state institution of the People's Consultative Assembly (MPR) which has launched and socialized the Four Pillars of National and State Life. One of the four pillars regulates Pancasila as the ideology and basis of the State